Soil stabilization linked to plant diversity and environmental context in coastal wetlands. (4th January 2016) - Ford, Hilary; Garbutt, Angus; Ladd, Cai; Malarkey, Jonathan; Skov, Martin W.
Abstract: Background: Plants play a pivotal role in soil stabilization, with above‐ground vegetation and roots combining to physically protect soil against erosion. It is possible that diverse plant communities boost root biomass, with knock‐on positive effects for soil stability, but these relationships are yet to be disentangled. Question: We hypothesize that soil erosion rates fall with increased plant species richness, and test explicitly how closely root biomass is associated with plant diversity. Methods: We tested this hypothesis in salt marsh grasslands, dynamic ecosystems with a key role in flood protection. Using step‐wise regression, the influences of biotic (e.g. plant diversity) and abiotic variables on root biomass and soil stability were determined for salt marshes with two contrasting soil types: erosion‐resistant clay (Essex, southeast UK) and erosion‐prone sand (Morecambe Bay, northwest UK). A total of 132 (30‐cm depth) cores of natural marsh were extracted and exposed to lateral erosion by water in a re‐circulating flume. Results: Soil erosion rates fell with increased plant species richness ( R 2 = 0.55), when richness was modelled as a single explanatory variable, but was more important in erosion‐prone ( R 2 = 0.44) than erosion‐resistant ( R 2 = 0.18) regions. As plant species richness increased from two to nine species·m −2, the coefficient of variation in soil erosion rate decreased significantly ( R 2 = 0.92). Plant species richness was a significant predictor of root biomass ( R 2 = 0.22). Step‐wise regression showed that five key variables accounted for 80% of variation in soil erosion rate across regions. Clay‐silt fraction and soil carbon stock were linked to lower rates, contributing 24% and 31%, respectively, to variation in erosion rate. In regional analysis, abiotic factors declined in importance, with root biomass explaining 25% of variation. Plant diversity explained 12% of variation in the erosion‐prone sandy region. Conclusion: Our study indicates that soil stabilization and root biomass are positively associated with plant diversity. Diversity effects are more pronounced in biogeographical contexts where soils are erosion‐prone (sandy, low organic content), suggesting that the pervasive influence of biodiversity on environmental processes also applies to the ecosystem service of erosion protection. Abstract : The complex relationship between biological and environmental drivers that determine ecosystem function is difficult to unravel. Here we present an erosion model that includes plant diversity and explains 80% of the variation in soil erosion rate in saltmarsh grasslands. When plant species richness was considered in isolation it explained 44% of erosion rate variation in the sandy region.